Bark Biometry Along the Stem for Three Commercial Tree Species in Romania - Vasilescu, Maria Magdalena (Forests, MDPIMDPI AG, Grosspeteranlage 5, CH-4052 BASEL, SWITZERLAND, 2024)
In general, bark serves a protective role for trees and is genetically determined. The quantification of bark based on biometric characteristics is linked to studies on the distribution of forest species across the globe and vegetation fires. In Romania, on the other hand, the improvement of the wood traceability system requires an increase in the accuracy of the estimation of the biometric characteristics of bark and, implicitly, of the volume of wood under the bark. The aim of this study was to develop more precise models for predicting bark thickness along the stem of three key Romanian species, taking into account a comprehensive range of models and stem sections, including those with a diameter over bark smaller than 8 cm, which have been excluded in previous studies. The study is based on two datasets, one containing the national measurements of three commercially valuable forest species, i.e., Norway spruce (Picea abies (L.) Karst), European beech (Fagus sylvatica L.), and pedunculate oak (Quercus robur L.) from 12,186 trees, and a second dataset containing the measurements from 61 logs of the same species at a specific forest site. A set of seven double bark thickness (DBT) estimation models with stem diameter over bark (DOB), DOB and total tree height (H), DOB and relative height along the stem (h/H), and diameter over bark at breast height (DBH) and DOB as predictors were used. The DBT models were evaluated using the coefficient of determination (R2), mean absolute error (MAE), root mean squared error (RMSE), the Akaike information criterion (AIC), and the Bayesian information criterion (BIC). This led to the selection of two more accurate models, Model 2 (based on a third-degree polynomial) and Model 3 (based on a logarithmic function), with DOB as the predictor. Relative double bark thickness (RDBT) and proportion of bark area (PBA) were also estimated using a sixth-degree polynomial and relative height as a predictor variable after stratifying the data by DBH classes to reduce variability. The results of this study indicate that there is a need to complete the database, for all three forest species of commercial value in Romania especially for large trees with DBH greater than 60-70 cm. The models obtained for PBA are of great use to the industry and the economy, in particular in the context of the traceability of wood. This is due to the fact that PBA can be equated with the proportion of bark volume (PBV), which describes the variation in the proportion of bark in the volume of the wood assortments along the stem. For a given DBH, PBA and PBV demonstrate minimal variability in sections from the tree's base to a relative height of 0.6; however, a pronounced increase is observed at crown level in sections above relative heights of 0.8.